Disobedience and Authority - Anthony M. Marino; John G. Matsusaka; Jan Zabojnik (Queen's University, Department of Economics, 2006)
This paper presents a theory of the allocation of authority in an organization in which centralization is limited by the agent's ability to disobey the principal. We show that workers are given more authority when they are costly to replace or do not mind looking for another job, even if they have no better information than the principal. The allocation of authority thus depends on external market conditions as well as the information and agency problems emphasized in the literature. Evidence from a national survey of organizations shows that worker autonomy is related to separation costs as the theory predicts.
Keywords: J63; M5; 330; Delegation; Authority; Separation Costs; Optimal employment contracts; Führungsstil; Autorität; Kooperative Führung; Prinzipal-Agent-Theorie; Theorie